Isolation and molecular characterization of L-Glutaminase producing bacteria isolated from red clay soil in Puncak Alam Selangor / Nur Syakila Rohawi - Rohawi, Nur Syakila (2015)
L-glutaminase was found as an effective enzyme in medical and food industry especially for cancer therapy and flavor enhancing agent become a remarkable attention for seeking more information of its uses and application as well as its origin of production. Various L-gutaminase producers from different sources have been studied from the past years. The aim of this study is to isolate L-glutaminase producing bacteria from the red clay soil using microbiological and molecular technique. L-glutaminase producer have been isolated from rapid screening culture using submerged fermentation method. Bacteria DNA of positive L-glutaminase producer were extracted and PCR was carried out to amplify 16S rDNA gene. PCR products were sequenced and the nucleotide sequence were determine using BLAST program in NCBI website. Out of 36 bacteria isolated, 4 bacteria were positive in screening test. Result of sequencing showed Comamonas sp, Stenotrophomonas sp and Pseudomonas sp were isolated. This shows that red clay soil has been inhabitant by L-glutaminase producing bacteria.